If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -88 = -8(r + 5) Reorder the terms: -88 = -8(5 + r) -88 = (5 * -8 + r * -8) -88 = (-40 + -8r) Solving -88 = -40 + -8r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '8r' to each side of the equation. -88 + 8r = -40 + -8r + 8r Combine like terms: -8r + 8r = 0 -88 + 8r = -40 + 0 -88 + 8r = -40 Add '88' to each side of the equation. -88 + 88 + 8r = -40 + 88 Combine like terms: -88 + 88 = 0 0 + 8r = -40 + 88 8r = -40 + 88 Combine like terms: -40 + 88 = 48 8r = 48 Divide each side by '8'. r = 6 Simplifying r = 6
| 6.8-4x=5(x-137) | | 4x+200=-3x+480 | | 7(1+5m)+6(1+4)=13 | | 9x-2y+18=0 | | X^2-6y-2x+1=0 | | 6x^2+34x-12=0 | | 2x^2-7=4 | | 15n-14n+3=18 | | -3u+6u=-20-1 | | -(x-2)=3 | | ln(5-2x)=-3 | | -8(-8-6x)=256 | | x-3=x-7 | | 5x+25+25=175 | | -17+6m=-3m+36 | | 1=-.25n+1 | | -2=k/5-5 | | -17+6m=3m+36 | | y^2=3y^2-72 | | -2(n-11)= | | 6x^3+22x^2-8x=0 | | 5(x+3)=15x+12-10x+3 | | 3g+3(-8+2g)=1-g | | -17+6m=3b+36 | | t^4-9t+8=0 | | 1/14*476 | | -9+8t=9t | | x(x+5)=270 | | h(6)=11 | | x-36=180 | | 13-t=16 | | -7(m+1)=-84 |